RELEVANSI KURIKULUM TAHUN 2002 PRODI PJKR TERHADAP KOMPETENSI LULUSANNYA - - Sukadiyanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
The expectation outcome of physical education health and recreation program (PJKR) FIKUNY as a physical educator teacher has four competence, that is (1) mastery of study area,(2) understanding of students, (3) mastery of educative learning, and (4) personalitydevelopment and professionalism. To be able to fulfill the competence standard andcertification as a beginner teacher it needed of some subject matter. The outcome target ofPJKR FIK UNY are saleable and competence in market work on their area. Because of thatrequire to supply by various skill and knowledge supporting the profession and duty as ateacher of physical education later. Pursuant to curriculum of PJKR 2002 there are somesubject matter less owning of relevance to candidate profession and duty as physical educator.On the contrary, there are some subject matter which still less of SKS and subject matterwhich ought to there is not yet written in curriculum PJKR 2002. Therefore, curriculum PJKR2002 specially and FIK UNY in general require to evaluate and studied to fulfill the competencestandard demand and certification as a beginner teacher of physical education.Keyword: PJKR 2002 curricullum, graduate competency.